The levadas and their implications for the dynamics of the slopes in the north of Portugal - Vieira, Antonio; Silva, Renato Emanuel; Costa, Francisco da Silva; Rodrigues, Silvio Carlos (Geopauta, 2024)
Hydraulic works are commonly investigated in terms of efficiency and installation and operating costs. However, it is also important to assess their impact on environmental aspects, especially their repercussions on river and slope systems. The aim of this study is to present an example of works that have been responsible for hydraulic, sedimentary, erosive and depositional changes in a stretch of a river channel in northern Portugal. Documentary analysis and field activities were carried out to identify the main changes suffered in the Levada do Piscaredo area. The research revealed that the ancient occupation represented by the levada generated significant changes, especially in the slopes, which underwent alterations both in their shape and in the erosive and depositional processes.